The Anti-Obesity Effect of Traditional Chinese Medicine on Lipid Metabolism - Fan, Qijing; Xu, Furong; Liang, Bin; Zou, Xiaoju (Frontiers in Pharmacology, 2021)
With the improvement of living conditions and the popularity of unhealthy eating and living habits, obesity is becoming a global epidemic. Obesity is now recognized as a disease that not only increases the risk of metabolic diseases such as type 2 diabetes (T2D), nonalcoholic fatty liver disease (NAFLD), cardiovascular disease (CVD), cancer, and so on, but obesity also negatively affects longevity and the quality of life. The traditional Chinese medicines (TCMs) are highly enriched in bio-active compounds and have been used for the treatment of obesity and obesity-related metabolic diseases over a long period of time. In this review, we selected the most commonly used anti-obesity or anti-hyperlipidemia TCMs and, where known, their major bioactive compounds. We then summarized their multi-target molecular mechanisms, specifically focusing on lipid metabolism, including the modulation of lipid absorption, reduction of lipid synthesis, increase of lipid decomposition, and lipid transportation, as well as the regulation of appetite. This review produces a current and comprehensive understanding of integrative and systematic mechanisms for the use of TCMs for anti-obesity. We also advocate taking advantage of TCMs as another therapy for interventions on obesity-related diseases, as well as stressing the fact that more is needed to be done, scientifically, to determine the active compounds and modes of action of the TCMs.